Authentic assessment strategies in Arabic language learning in the digital era - Mulyani, Rinda Eka; Habib, Ikhwanul; Hadi, Nur (Abjadia : International Journal of Education, 2025)
Authentic assessment is an evaluative approach that emphasizes real-world skills, aligns with real-life contexts, and encompasses both the process and outcomes of learning. As a form of assessment adapted to real-life situations, it is expected to effectively address the challenges of the digital era. This study aims to describe authentic assessment strategies in Arabic language learning in the digital age. Employing a descriptive qualitative approach, data were collected through a literature review of various sources, including books, articles, and journals, and analyzed using the Miles and Huberman model. The findings indicate that authentic assessment differs from traditional assessment as it evaluates students based on the application of knowledge through meaningful tasks such as projects, portfolios, presentations, and debates. In Arabic language learning, authentic assessment can be developed based on the four language skills (maharah lughawiyah). Strategies for authentic assessment in the digital era can utilize technologies such as podcasts, videos, online story websites, and collaborative platforms to create relevant and engaging learning experiences.